Effect of palm kernel meal level on feed intake, body composition, and hepatic histopathology features of Kelabau (Osteochilus melanopleurus) - Kusdianto, Heru; Almadi, Ismail Fahmy; Anugerah, Putri; Pratama, Jordan; Aida, Noor Fatmi (Universitas Batangahari Jambi, 2026)
The effect of including palm kernel meal (PKM) on the feed intake, body composition, and hepatic histopathology of Kelabau (Osteochilus melanopleurus) was experimentally studied in a 50-day feeding trial. Four experimental diets were formulated in dry pellet form with a protein content of approximately 30%. The treatments consisted of varying PKM concentrations (0%, 5%, 15%, and 20%). The experimental fish were reared in 12 aquaria (30 x 30 x 40 cm³) and fed to satiation three times daily. A Completely Randomized Design (CRD) was employed for this research. Results indicated that the treatments had no significant effect (P > 0.05) on total feed intake. However, feed consumption tended to decrease as PKM content increased. Furthermore, PKM inclusion significantly influenced body composition; higher PKM levels led to a sharp increase in Nitrogen-Free Extract (NFE), while simultaneously reducing body protein and lipid content. Additionally, increased PKM levels were observed to cause hepatic lipid accumulation and the displacement of cell nuclei to the periphery.